Crisis, Committees and Consultants: The Rise of Value-For-Money Auditing in the Federal Public Sector in Canada - Free, Clinton (Journal of business ethics, 2013)
This paper investigates the key drivers behind the origins of value-for-money (VFM) audit in Canada and the aims, intents, and logics ascribed by the original proponents. Drawing on insights from governmentality and New Public Management, the paper utilizes analysis methods adapted from case study research to review a wide range of primary documentation (e.g., Hansards from the Public Accounts Committee, House of Commons debates, the so-called Wilson report and the FMCS study) and secondary documentation (newspaper articles, Office of the Auditor General internal publications, journal articles). Major findings indicate a rise of a management consulting culture within the Auditor General’s office following the appointment of James Johnson Macdonell. VFM legislation effectively operationalized practices drawn from management consulting expertise by invitation of the consultant. It was offered as an answer to the growing scope and size of government, which had become problematized by the Auditor General in terms of parliament losing control over the public purse. The Auditor General’s invocation of financial crisis led to a substantial broadening of mandate and increase in resources for that office.